Flavour science : recent developments - Taylor, A. J.; Mottram, D. S. (The Royal Society of Chemistry, 1996)
This volume contains the 86 lectures, posters and workshop presentations made at the 8th Weurman Flavour Research Symposium. These are mainly research papers and are divided into seven subject areas reflecting the major divisions of flavour science.